2016
DOI: 10.1089/apc.2015.0351
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Profiles of Antiretroviral Therapy Adherence Among African American Adolescents and Young Adult Males Living with HIV

Abstract: Adherence to antiretroviral therapy (ART) is crucial for thwarting HIV disease progression and reducing secondary HIV transmission, yet youth living with HIV (YLH) struggle with adherence. The highest rates of new HIV infections in the United States occur in young African American men. A sample of 387 HIV-positive young African American males on ART was selected from a cross-sectional assessment of (YLH) receiving medical care within the Adolescent Trials Network for HIV/AIDS Interventions (ATN) from 2010 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 56 publications
(94 reference statements)
4
39
1
Order By: Relevance
“…These findings are consistent with evidence from a large multi-site study, demonstrating that adolescent and young adult participants least likely to be adherent had higher psychological distress and used marijuana weekly. More specifically, a frequency of substance use variable, marijuana use during the past 3 months, was the strongest independent predictor of ART adherence, yielding moderate effect strength sensitivity [6]. There is also compelling evidence to show that as the number of psychosocial conditions increases, there is a decreased likelihood of ART adherence [69].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with evidence from a large multi-site study, demonstrating that adolescent and young adult participants least likely to be adherent had higher psychological distress and used marijuana weekly. More specifically, a frequency of substance use variable, marijuana use during the past 3 months, was the strongest independent predictor of ART adherence, yielding moderate effect strength sensitivity [6]. There is also compelling evidence to show that as the number of psychosocial conditions increases, there is a decreased likelihood of ART adherence [69].…”
Section: Discussionmentioning
confidence: 99%
“…Staggering disparities along the HIV care cascade exist for HIV-infected youth living in the US including lack of sustained HIV RNA viral suppression, adherence to antiretroviral therapy (ART), and retention in care [3, 4]. Antiretroviral therapy is recommended for all HIV-infected individuals irrespective of HIV biomarkers [5], and optimal HIV disease management is contingent upon high levels of adherence, greater than >95% to prescribed unboosted protease inhibitor (PI) containing ART regimens, and 80% adherence for boosted PI ART regimens [6, 7]. However, despite the availability of effective ART, estimates of HIV RNA viral suppression range from 30.5% [4] to less than six percent among HIV-infected youth [3], and uncontrolled HIV replication imposes an increased risk of morbidity and mortality at all CD4-T lymphocyte strata [8].…”
Section: Introductionmentioning
confidence: 99%
“…6,22,31,34,35 A recent study found that black adolescents and young adults with HIV who had higher psychological distress and reported higher frequency of cannabis use were less likely to be adherent to antiretroviral treatment. 36 It is possible that this and other factors may be driving the association between age and viral suppression.…”
Section: Care Retention and Viral Suppression Disparitiesmentioning
confidence: 99%
“…This relationship has also been further explored among HIV-infected Black adolescents and young adults, where a high level of psychological distress and marijuana use weekly or more frequently for at least 3 months were predictive of ART non-adherence [69% accuracy; 30]. Further, 24% more of these high distress, frequent marijuana using youth were ARV non-adherent when comparing levels of reported self-efficacy to attend appointments, with high-self efficacy being protective.…”
Section: Resultsmentioning
confidence: 99%
“…HIV-infected individuals may use marijuana to mediate HIV symptoms and medication side effects [39, 42, 43], and users have been shown to be more likely to be avoidant, avoid stressors, and negative experiences [44] which may contribute to medication non-adherence. Further, while substance use has consistently been shown to impact ARV adherence, there may be attributes of use (e.g., frequency) or treatment adherence (e.g., self-efficacy), as demonstrated by Gross and colleagues [30], that may be stronger predictors of associations between medication adherence and marijuana use.…”
Section: Discussionmentioning
confidence: 99%